O blog na EJA autobiografia e ação emancipadora - Bersi, Rodrigo Martins (Editora Oficina Universitária, 2020)
The book "O BLOG NA EJA: Autobiografia e Ação Emancipadora" discusses a pedagogical action in youth and adult education in the context of its consolidation as a Subjective Public Law, based on Cultural Historical Theory, Philosophy of Language and Qualitative Research. Its main points of reflection are the legacy of Vygotsky in thinking about the development of subjects through language, Paulo Freire in guiding the methods of pedagogical action within the scope of EJA and the study of discursive genres in Bakhtin, focusing on the production of autobiographies. It is guided by a perspective of comprehensive training and liberating practice for the emancipation of subjects, in which individuals become motivated by the sense of learning in an omnilateral perspective, forming themselves for multiple needs, revealing the reality in which they are inserted, recognizing themselves as historical and cultural subjects in society. Therefore, learning in EJA must be pleasurable and understood as a human activity whose genesis is located in the context of articulation between motives and learning needs, in the generation of ideas, articulation and negotiation of meanings. Discussing youth and adult education of a developmental nature, the work is of interest both to teachers who teach in EJA and to professionals in educational networks involved with technical-pedagogical guidance and initial or continuing education of educators.